21.5k views
5 votes
Given f(x) = 2x - 7 and g(x) = 3x + 2, find (fog)(x).​

1 Answer

3 votes

Answer:

(fog)(x)=6x-3

Explanation:

In this problem, we are looking to find f of g of x. Simply put, we just have to plug g(x) into f(x). Whereever there is an x in f(x), we will replace with g(x).


(fog)(x)= 2(g(x))-7\\(fog)(x)=2(3x+2)-7\\(fog)(x)=6x+4-7\\(fog)(x)=6x-3

I hope this helps! Let me know if you have any questions :)

User Houdmont
by
6.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.